A sequential principal component-based algorithm for optimal lineup and batting order selection in one day international cricket for Bangladesh. (4th July 2019) - Shanto, Shantonu Islam; Awan, Nabil
ABSTRACT: Determining the optimal lineup and batting order have ever been a challenge in ODI cricket for the Bangladesh team management. Over the years, we have seen them trying different batsmen in various positions and the process is still going on. While a stable batting order is crucial for long-term success in the game, this is understandably a difficult problem to decide because there are so many determinants that a team needs to consider. These determinants are usually correlated and optimally mapping them into a single dimension can help us make the problem easier and comment about what's best on statistical grounds. In this article, we propose a sequential principal component-based algorithm to evaluate the players' performances in batting and bowling, and to order the batting positions of the recent Bangladesh national cricket team players to find the best squad. In particular, the first principal component explains a substantial portion of the variation in a linear combination of some commonly used measures of cricket prowess. The algorithm focuses on obtaining the best batting line-up using successive principal components for each position. We also layout different strategies of team formation based on the bowling performances for different conditions and pitches.